DSP Toxin Distribution across Organs in Mice after Acute Oral Administration - Louzao, M. Carmen (Mar Drugs, 2021)
Okadaic acid (OA) and its main structural analogs dinophysistoxin-1 (DTX1) and dinophysistoxin-2 (DTX2) are marine lipophilic phycotoxins distributed worldwide that can be accumulated by edible shellfish and can cause diarrheic shellfish poisoning (DSP). In order to study their toxicokinetics, mice were treated with different doses of OA, DTX1, or DTX2 and signs of toxicity were recorded up to 24 h. Toxin distribution in the main organs from the gastrointestinal tract was assessed by liquid chromatography-mass spectrometry (LC/MS/MS) analysis. Our results indicate a dose-dependency in gastrointestinal absorption of these toxins. Twenty-four hours post-administration, the highest concentration of toxin was detected in the stomach and, in descending order, in the large intestine, small intestine, and liver. There was also a different toxicokinetic pathway between OA, DTX1, and DTX2. When the same toxin doses are compared, more OA than DTX1 is detected in the small intestine. OA and DTX1 showed similar concentrations in the stomach, liver, and large intestine tissues, but the amount of DTX2 is much lower in all these organs, providing information on DSP toxicokinetics for human safety assessment.